Quota Formula Review : Further Considerations. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
This paper is a Statistical Appendix to complement the Quota Formula Review-Further Considerations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Drop Var; GDP Blend; PP; PPP GDP; W GDP; Afghanistan, Islamic Republic of